Grey zone simulations of the morning convective boundary layer development. Issue 9 (5th May 2016) - Efstathiou, G. A.; Beare, R. J.; Osborne, S.; Lock, A. P.
Abstract: Numerical simulations of two cases of morning boundary layer development are conducted to investigate the impact of grid resolution on mean profiles and turbulent kinetic energy (TKE) partitioning from the large eddy simulation (LES) to the mesoscale limit. Idealized LES, using the 3‐D Smagorinsky scheme, is shown to be capable of reproducing the boundary layer evolution when compared against measurements. However, increasing grid spacing results in the damping of resolved TKE and the production of superadiabatic temperature profiles in the boundary layer. Turbulence initiation is significantly delayed, exhibiting an abrupt onset at intermediate resolutions. Two approaches, the bounding of vertical diffusion coefficient and the blending of the 3‐D Smagorinsky with a nonlocal 1D scheme, are used to model subgrid diffusion at grey zone resolutions. Simulations are compared against the coarse‐grained fields from the validated LES results for each case. Both methods exhibit particular strengths and weaknesses, indicating the compromise that needs to be made currently in high‐resolution numerical weather prediction. The blending scheme is able to reproduce the adiabatic profiles although turbulence is underestimated in favor of the parametrized heat flux, and the spin‐up of TKE remains delayed. In contrast, the bounding approach gives an evolution of TKE that follows the coarse‐grained LES very well, relying on the resolved motions for the nonlocal heat flux. However, bounding gives unrealistic static instability in the early morning temperature profiles (similar to the 3‐D Smagorinsky scheme) because model dynamics are unable to resolve TKE when the boundary layer is too shallow compared to the grid spacing. Key Points: Two approaches to model subgrid diffusion at grey zone resolutions are compared in simulating two cases of an evolving boundary layer Bounding approach significantly improves spin‐up; blending better simulates early morning profiles Proposed methods exhibit particular strengths and weaknesses indicating the level of compromise currently needed in high‐resolution NWP